FORMULATION OF MAKING COW MILK KEFIR WITH ADDITION TO PINEAPPLE EXTRACT AS SUGAR REPLACEMENT - Sholati Muzdalifah; Retno Budi Lestari; Duta Setiawan (Fakultas Pertanian Universitas Tanjungpura, 2020)
This study aim to determine the addition of pineapple extract as a sugar subtitute for physico-chemical and organoleptic kefir of cow’s milk. The study was conducted at the Animal Husbandry Laboratory of the Faculty of Agriculture, Tanjungpura University, Pontianak. The research design used was a randomized block design (RBD) with 5 treatments and 5 replications for each treatment, namely P0 = (6% sugar + 0% pineapple extract)), P1 = (4.5% sugar + 1.5% pineapple extract), P2 = (3% sugar + 3% pineapple extract), P3 = (1.5% sugar + 4.5% pineapple extract), P4 = (0% sugar + 6% pineapple extract). Parameters observed were reducing sugars, pH, ethanol levels, total acids, proteins and organoleptics. Then the data were analyzed statistically using the F Test by comparing table F at the 5% level and continued with the HSD Test if it had a significant effect. The results showed that the addition of pineapple extract had a significant effect on pH, reducing sugar, total acid, ethanol content and cow milk kefir protein but had no significant effect on organoleptics which included preference for cow milk kefir. The best treatment from the research that has been done is the results of the calculation of the best treatment value NP) at 3% treatment resulting in pH 4,36%, total acid 0.66%, ethanol 9,34%, reduced sugar 18,26%, protein 4,22%, texture 3,84 (rather like), flavor 3.32 (rather like), preference 3.48 (rather like), and aroma 3.48 (rather like) Keywords: cow’s milk, kefir seed, pineapple.